Therapeutic potential of Polyalthia cerasoides stem bark extracts against oxidative stress and nociception - Goudarshivananavar, B. C. (Anc Sci Life, 2015)
BACKGROUND: Polyalthia cerasoides is a medicinal plant known for its ethnopharmacological importance. Despite this, investigation related to its therapeutic benefit is still unexplored. AIM: To evaluate the stem bark extracts of Polyalthia cerasoides for pharmacological activities relating to inflammation, nociception and oxidative stress using in vivo and in vitro models. MATERIALS AND METHODS: Pet ether, ethyl acetate and chloroform fractions of the stem bark were evaluated for anti-inflammatory activity by carrageenan-induced hind paw edema in rats. Anti-nociceptive activity in mice was assessed using thermally and chemically induced analgesic models. The free radical quenching potential of the extracts was initially analyzed using the in vitro DPPH photometric assay, Hydroxyl radical scavenging and Lipid Peroxidation assays. Then modulatory effect of the extracts on in vivo antioxidant system was evaluated by carbon tetrachloride induced hepatotoxicity and subsequent measurements of antioxidant enzymes such as Superoxide dismutase, Catalase and Peroxidase from the liver homogenate. RESULTS: Among the tested fractions, ethyl acetate extract had substantially inhibited the inflammation by 68.5% that was induced by subcutaneous carrageenan injection whereas pet ether and chloroform extract showed only minimal inhibitory effect. Investigation of the anti-nociceptive activity revealed that the ethyl acetate fractions had significantly repressed the algesia in both the analgesic experimental models. In vitro and in vivo individual antioxidant assays demonstrated that the ethyl acetate fraction has strong free radical quenching potential which also restores the endogenous hepatic enzymes. CONCLUSION: The ethyl acetate fraction enriched with flavinoids and steroids from Polyalthia cerasoides stem bark has potent bioactivity to combat inflammation, ROS and pain. This needs further characterization for potential therapeutic applications.